Determinants and practices towards cyber supply chain performance with cyber supply chain visibility as a mediator - Anisha Banu, Dawood Gani (2022)
Manufacturing industry is one of the most targeted industries for cyberattacks, causing losses in millions and jeopardizing nations critical infrastructure. Despite the initiatives taken by Malaysian government, Malaysia ranks 11th most breached countries in the world. Thus, this study was undertaken to shed light on the preparedness level of Malaysia’s manufacturing industry in facing disruptions in their cyber supply chain (CSC). In addition, the drivers for cyber supply chain risk management (CSCRM) practices adoption and understanding what kind of policies, actions and system readiness should be in effect to achieve the security, agility, robustness, and resilience of the entire supply chain was also explored. As such, a theoretical framework on the mediating role of CSC visibility with CSCRM practices and CSC performance was developed and examined empirically through this study. A survey method was used to gather data from manufacturing firms that were registered with FMM. A total of 130 respondents’ data was analysed using SPSS version 24 and SmartPLS 3.2.8 software to answer the research objectives stipulated. In addition, the role of CSC visibility as a mediator in achieving CSC performance was also tested. While many scholars have theorized that the CSC visibility level is a useful measure for the firm to assess the effectiveness of the CSCRM practices it has implemented to improve its CSC performance, through this study, it has been successfully examined empirically. The result indicated that CSC visibility does mediate between CSCRM practices and CSC performance. Moreover, there is also a strong direct relationship between CSC visibility and CSC performance as theorized, giving affirmations to manufacturing firms that investments and policies devised to improve CSC visibility will fare well in achieving a resilient, robust, agile, and secure supply chain. However, the adoption level of CSCRM practice among the manufacturing firms in Malaysia has a median level of four, signifying ample opportunity to educate and amplify the CSC security within the manufacturing industry in Malaysia to be able to withstand growing malicious attacks.